DIGITAL TECHNOLOGY ADOPTION AND PERFORMANCE OF WOMEN ENTREPRENEURS: FINDINGS FROM EAST JAVA - Feranita, Nungky Viana; Dwimahendrawan, Andrias; Asmuni, Asmuni (Institut Teknologi dan Bisnis Asia Malang, 2024)
This research aims to analyze the influence of digital technology adoption on the performance of women entrepreneurs. This type of research is quantitative with a causal associative type. The population in this study was 394 women entrepreneurs in East Java Province. The sampling technique used purposive sampling to obtain a sample size of 268 respondents. Data collection uses questionnaires and data analysis techniques using PLS-SEM. The research results show that digital technology adoption has a positive and significant effect on the performance of women entrepreneurs in East Java Province. These results provide a practical contribution, namely that women entrepreneurs are encouraged to adopt digital technology so that it can help them improve their business performance.